In vitro antimicrobial and α-glucosidase inhibitory potential of enantiopure cycloalkylglycine derivatives: Insights into their in silico pharmacokinetic, druglikeness, and medicinal chemistry properties - Adel Kadri&, Kaiss Aouadi& (Journal of Applied Pharmaceutical Science, 2020)
The present investigation deals with the evaluation for the first time of the in vitro antimicrobial and α-glucosidase inhibitory potential of a series of 15 enantiopure cycloalkylglycines using agar well diffusion and spectrophotometric methods, respectively. The obtained results were compared to the positive controls. The antimicrobial results revealed that all compounds exerted strongly inhibitory activity, especially against Gram-positive bacterial strains with the most potent activity was ascribed to α-γ-hydroxy-α-amino acids 11–14 [minimum inhibitory concentration (MIC) = 1.58– 12.50 mg/ml, minimum bactericidal concentration (MBC) = 3.17–100 mg/ml, and minimum fungicidal concentration (MFC) = 6.25–50 mg/ml], followed by both isoxazolidine 5–9 (MIC = 1.58–12.50 mg/ml, MBC = 6.25–100 mg/ml, and MFC = 25–100 mg/ml) and isoxazine 10 (MIC = 3.17–12.50 mg/ml, MBC = 3.17–50 mg/ml, and MFC = 25–50 mg/ml) compounds, and slightly inhibitory effect with α-amino-γ-lactones series 1–4 (MIC = 3.17–25 mg/ml, MBC = 6.25–100 mg/ml, and MFC = 25–100 mg/ml). All the derivatives exhibited a potent α-glucosidase inhibitory activity with compound 10 (IC50 = 30.1 ± 0.6 μM) was found to be the most active. The druglikeness and pharmacokinetic profiles have been also predicted. The in silico results indicate that all derivatives showed a resemblance with several parameters of the antimicrobial standards, especially in terms of molecular property, bioavailability, lipophilicity, medicinal chemistry, and enzymatic inhibitory effects as well as they agree with the different drug discovery rules such as Lipinski (Pfizer), Ghose (Amgen), Veber (GlaxoSmithKline), Egan (Pharmacia), and Muegge (Bayer) displaying a higher druglikeness behavior.
Keywords: Cycloalkylglycines, in vitro antimicrobial, α-glucosidase inhibitory potential, druglikeness, medicinal chemistry.